The Impact of Mental Health on The Immune System During the Covid-19 Pandemic - Caroline Dharmawan; Niken Bayu Argaheni (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Background: The outbreak of Covid-19 virus in various countries has caused a lot of very significant changes. This Covid-19 outbreak has had profound impact on various aspects of life, from an economic, political, social perspective, and especially in terms of public health, especially in Indonesia. The symptoms caused by the Covid-19 virus are not only focused on physical health, but also affect psychological health. Goal: To prove that mental health affects immunity system.Methods: Systematic review.Result: The lower positive attitude, lack of social support, poor strategies in reducing the spread of virus, working with Covid-19 infected patient, causes high levels of stress. Conclusion: Prolonged stress and anxiety is decreasing body’s immune respons, thus making the body susceptible to disease. So that in overcoming this pandemic, beside focused on physical health, it is necessary to consider mental and psychosocial health Keywords: Mental Health, Covid-19, Immune system